STUDI KASUS: OSTEOCHONDROMA SCAPULA DAN TIBIA FIBULA PADA REMAJA USIA 14 TAHUN - Tandy Chintya Tanaji; Firdha Leonita; Partogi Napitupulu; Astien Astien; Revalita Wahab; Mulia Rahmansyah; Gupita Nareswari (Fakultas Kedokteran Universitas Trisakti, 2025)
Multiple Hereditary Exostoses (MHE) is an autosomal dominant inherited genetic condition characterized by multiple exostoses (or osteochondromas). Genetic analysis had identified a certain type of mutated Exostosin genes, can potentially cause exostoses. A 14 years old boy referred to our hospital with a chronic hard palpable lump on his left back and right lower limb in the past 10 years, and was gradually increased in size. Laboratory test which consists of complete blood count, urinalysis, and renal function test were normal. A radiographic examination of the related skeleton demonstrated multiple osteochondromas of scapula and tibia fibula. As a consequence of mutations in the Exostosin 1 and Exostosin 2 genes, chondrocytes exhibiting shortened Heparan Sulfate chains are present in this region. In the later stages, these cells develop exostoses. Multiple Hereditary Exostoses may involve different bone locations and could be diagnosed using various medical imaging modalities, however plain radiography x-ray was already sufficient enough to conclude the abnormality. Sessile lesions were much more common than pedunculated in Multiple Hereditary Exostoses, however Sessile lesions bear a higher risk of malignant transformation into chondrosarcoma. Upon early detection, the prognosis for patients who have chondrosarcoma was favorable. Multiple Hereditary Exostoses is a rare bone disorder marked by the development of non-cancerous tumors near the growth plates of bones. This condition can greatly affect an individual's quality of life, resulting in restricted mobility, skeletal abnormalities, ongoing pain, inhibited growth, and the risk of the exostoses becoming malignant.